2012
DOI: 10.1088/0963-0252/21/3/034002
|View full text |Cite
|
Sign up to set email alerts
|

Argon metastable dynamics in a filamentary jet micro-discharge at atmospheric pressure

Abstract: Abstract.Space and time resolved concentrations of Ar ( 3 P 2 ) metastable atoms at the exit of an atmospheric pressure radio-frequency micro-plasma jet were measured using tunable diode laser absorption spectroscopy. The discharge features a coaxial geometry with a hollow capillary as an inner electrode and a ceramic tube with metal ring as outer electrode. Absorption profiles of metastable atoms as well as optical emission measurements reveal the dynamics and the filamentary structure of the discharge. The a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 21 publications
1
38
1
Order By: Relevance
“…Thus, the highest production rate of Ar m is found at high electron densities, i.e., during the ignition of each plasma filament. Additionally, the Ar m production is possible as a result of resonant neutralisation, where Ar ions recombine with the negative surface charge on the dielectric substrate and form an Ar m [34]. Due to the direct ignition on the substrate surface, a considerable Ar m density can be assumed to exist in the near-surface area.…”
Section: B Hybrid Laser Plasma Ablation Resultsmentioning
confidence: 99%
“…Thus, the highest production rate of Ar m is found at high electron densities, i.e., during the ignition of each plasma filament. Additionally, the Ar m production is possible as a result of resonant neutralisation, where Ar ions recombine with the negative surface charge on the dielectric substrate and form an Ar m [34]. Due to the direct ignition on the substrate surface, a considerable Ar m density can be assumed to exist in the near-surface area.…”
Section: B Hybrid Laser Plasma Ablation Resultsmentioning
confidence: 99%
“…The existence of such species in the near-surface area can most likely be assumed due the direct plasma ignition on the substrate based on electron excitation and ion-impact excitation in the plasma sheath close to the sample surface [18] and/or resonant neutralisation. In the last case, argon metastables are provided as a result of the recombination of argon ions with the negative surface charge on the dielectric sample [19]. However, both effects, ion bombardment and de-excitation of argon species, should result in an almost uniform material removal.…”
Section: Discussionmentioning
confidence: 99%
“…However, Ar APPJs are often filamentary, and the accurate mapping of Ar m absolute densities is therefore challenging. Different works have shown that this can be achieved using TDLAS in specific APPJ configurations . However, the vast majority of published studies refer to APPJs driven mostly by rf or kHz‐sinusoidal voltages without studying the effect of different targets.…”
Section: Introductionmentioning
confidence: 99%
“…in the absence of a target) and in the presence of targets (grounded or at floating potential). However, Ar APPJs are often filamentary, [3,[26][27][28][29] and the accurate mapping of Ar m absolute densities is therefore challenging. Different works have shown that this can be achieved using TDLAS in specific APPJ configurations.…”
mentioning
confidence: 99%